Male circumcision for prevention of heterosexual acquisition of HIV in men. - Siegfried, N; Muller, M; Volmink, J; Deeks, J; Egger, M; Low, N; Weiss, H; Walker, S; Williamson, P (2003)
BACKGROUND: The findings from observational studies, reviews and meta-analyses, supported by biological theories, that circumcised men appear less likely to acquire human immunodeficiency virus (HIV) has contributed to the recent ground swell of support for considering male circumcision as a strategy for preventing sexually acquired infection. We sought to elucidate and appraise the global evidence from published and unpublished studies that circumcision can be used as an intervention to prevent HIV infection. OBJECTIVES: 1) To assess the evidence of an interventional effect of male circumcision for preventing acquisition of HIV-1 and HIV-2 by men through heterosexual intercourse 2) To examine the feasibility and value of performing individual person data (IPD) meta-analysis SEARCH STRATEGY: We searched online for published and unpublished studies in The Cochrane Library (issue 2, 2002), MEDLINE (April 2002), EMBASE (February 2002) and AIDSLINE (August 2001). We also searched databases listing conference abstracts, scanned reference lists of articles and contacted authors of included studies. SELECTION CRITERIA: We searched for randomized and quasi-randomized controlled trials of male circumcision or, in their absence, observational studies that compare acquisition rates of HIV-1 and HIV-2 infection in circumcised and uncircumcised heterosexual men. DATA COLLECTION AND ANALYSIS: Independent reviewers selected studies, assessed study quality and extracted data. We stratified studies based on study design and on whether they included participants from the general population or high-risk groups (such as patients treated for sexually transmitted infections). We expressed findings as crude and adjusted odds ratios (OR) together with their 95% confidence intervals (CI) and conducted a sensitivity analysis to explore the effect of adjustment on study results. We investigated whether the method of circumcision ascertainment influenced study outcomes. MAIN RESULTS: We identified no completed randomized controlled trials. Three randomized controlled trials are currently underway or commencing shortly. We found 34 observational studies: 16 conducted in the general population and 18 in high-risk populations. It seems unlikely that potential confounding factors were completely accounted for in any of the included studies. In particular, important risk factors, such as religion and sexual practices, were not adequately accounted for in many of the included studies. General population study results:The single cohort study (N = 5516) showed a significant difference in HIV transmission rates between circumcised and uncircumcised men [OR = 0.58; 95% CI: 0.36 to 0.96]. Results for the 14 cross-sectional studies were inconsistent, with point estimates for unadjusted odds ratios varying between 0.28 and 1.73. Six studies had statistically significant results, four in the direction of benefit and two in the direction of harm. The test for heterogeneity between the cross-sectional studies was highly significant (chi-square = 77.59; df = 13; P-value < 0.00001). Nine studies reported adjusted odds ratios with eight in the direction of benefit, ranging from 0.26 to 0.80. Use of adjusted results tended to show stronger evidence of an association although they remained heterogenous (chi-square = 75.2; df = 13; P-value < 0.00001). Only one case-control study was found (N = 51) which had a non-significant result [OR = 1.90; 95% CI: 0.50 to 7.20]. High-risk group study results:The four cohort studies identified found a protective effect from circumcision with point estimates for unadjusted odds ratios varying from 0.10 to 0.39. Two of these studies had statistically significant results. Two studies reported adjusted odds ratios, both protective with one being significant. The chi-square test for between-study heterogeneity was not significant (chi-square = 5.21; df = 3; P-value = 0.16). All eleven cross-sectional studies reporting unadjusted results found benefit from circumcision, eight of which had statistically significant results. Estimates of effnal studies reporting unadjusted results found benefit from circumcision, eight of which had statistically significant results. Estimates of effect varied from an unadjusted odds ratio of 0.10 to 0.66. Between-study heterogeneity was significant with the chi-square = 29.77; df = 10; P-value = 0.0009. Four of these studies reported adjusted odds ratios ranging from 0.20 to 0.59 and all were significant. One additional cross-sectional study only reported an adjusted odds ratio in the direction of benefit which was statistically significant. All three case-control studies found a protective effect of circumcision on HIV status, two being statistically significant. Point estimates varied from unadjusted odds ratios of 0.37 to 0.88. One reported an adjusted odds ratio showing a significant protective effect. Adverse effects:No studies reported on the adverse effects of circumcision. In most studies, circumcision had taken place during childhood or adolescence before the studies commenced. REVIEWER'S CONCLUSIONS: We found insufficient evidence to support an interventional effect of male circumcision on HIV acquisition in heterosexual men. The results from existing observational studies show a strong epidemiological association between male circumcision and prevention of HIV, especially among high-risk groups. However, observational studies are inherently limited by confounding which is unlikely to be fully adjusted for. In the light of forthcoming results from RCTs, the value of IPD analysis of the included studies is doubtful. The results of these trials will need to be carefully considered before circumcision is implemented as a public health intervention for prevention of sexually transmitted HIV.